“Nóis é terrívi, se nóis fala que faz, nóis faz": o acampamento Elizabeth Teixeira em Limeira-SP e a construção da escola como espaço público de auto-organização e educação popular - Rodrigues, Tessy Priscila Pavan de Paula (2016)
The study presented in this paper was aimed at uncovering the most relevant social relations contributing to the creation of a self-organized popular education school in the Elizabeth Teixeira (ET) encampment in Limeira (São Paulo), whose construction was inspired on the fight for Agrarian Reform undertaken by Brazil's Landless Workers Movement (MST). In this sense, the school was understood as a unification of multiple determinations that constituted the camp itself, where the SelfOrganization and Popular Education elements were seen as roots and fruits of this process, simultaneously projecting themselves as technical categories and serving as foundations for this study. The analysis considered mainly the relationship between the three following collective subjects: the inhabitants of the Elizabeth Teixeira encampment, the MST and Universidade Popular (UP), a collective project conducted by popular educators. UP’s reports and accounts were used as source for the present research, as well as videos recorded by encampment supporters and memories recalled during the Círculos de Memória Investigativos (meetings of investigative memory) organized with groups which took part in the construction of the school. The study revealed that the school (or “escolinha”, “little school”, as it’s called among participants) is a hub of forces that helps maintain the vitality of the encampment. The popular feature of the educational process analyzed became evident through some of the paths taken from collective decisions that attempted to deal with issues arising during the process of construction of the school. This popular characteristic rebuilds the meaning of “public” in a space that in nine years has never been legally recognized by the State.